Fundamentals in Information Theory and Coding - Borda, Monica; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The work introduces the fundamentals concerning the discrete information theory (measures of discrete information, mathematical modeling of discrete memoryless/memory sources and of discrete transmission channels) and the coding theory with its main components: compression, error control and encryption. The understanding of the theoretical matter is supported by many examples. One particular emphasis is put on the explanation of Genomic Coding. Many examples throughout the book are chosen from this particular area and several parts of the book are devoted to this exciting implication of coding. The book is interesting and highly valuable for educational purposes for students and all those who need basics in information theory and coding. Monica E. Borda is Professor in Information Theory and Coding, Cryptography and Genomic Signal Processing at the Technical University of Cluj-Napoca, Romania, having more than 30 years experience of education and research in the topics covered by the book. She has conducted research and Ph.D. thesis in coding theory, nonlinear signal and image processing, image watermarking, genomic signal processing, having authored and coauthored more than 100 research papers in national and international journals and conference proceedings. She is author and coauthor of 5 books in the mentioned fields.
Information trans mission systems (ITS) -- Statistical Information Model of an ITS -- Source Coding -- Coding for Noiseless Channels -- Cryptography Basics -- Channel Coding.
Keywords: Engineering; Coding theory; Bioinformatics; Engineering; Signal, Image and Speech Processing; Coding and Information Theory; Bioinformatics